Cancer epidemiology in the small nations of Pacific Islands. (October 2017) - Tervonen, Hanna; Foliaki, Sunia; Bray, Freddie; Roder, David
Highlights: Recorded cancer incidence in the Pacific Islands was relatively low, with New Caledonia and French Polynesia being exceptions. Nevertheless, cancer has an important contribution to mortality in the region. Further endeavors are needed to develop population-based cancer registration and to improve data quality and registration coverage. Abstract: Background: Pacific island countries and territories (PICTs) comprise 20, 000–30, 000 islands in the Pacific Ocean. PICTs face challenges in relation to small population sizes, geographic dispersion, increasing adoption of unhealthy life-styles and the burden of both communicable and non-communicable diseases, including cancer. This study reviews data on cancer incidence and mortality in the PICTs, with special focus on indigenous populations. Methods: PICTs with populations of <1.5 million ('small nations') were included in this study. Information on cancer incidence and mortality was extracted from the GLOBOCAN 2012 database. Scientific and grey literature was narratively reviewed for publications published after 2000. Results: Of the 21 PICTs, seven countries were included in the GLOBOCAN 2012 (Fiji, French Polynesia, Guam, New Caledonia, Samoa, Solomon Islands, Vanuatu). The highest cancer incidence and mortality rates were reported in New Caledonia (age-standardized incidence and mortality rates 297.9 and 127.3 per 100.000) and French Polynesia (age-standardized incidence and mortality rates 255.0 and 134.4 per 100.000), with relatively low rates in other countries. Literature indicated that cancer was among the leading causes of deaths in most PICTs; thus they now experience a double burden of cancers linked to infections and life-style and reproductive factors. Further, ethnic differences in cancer incidence and mortality have been reported in some PICTs, including Fiji, Guam, New Caledonia and Northern Mariana Islands. Conclusion: Cancer incidence in the PICTs was recorded to be relatively low, with New Caledonia and French Polynesia being exceptions. Low recorded incidence is likely to be explained by incomplete cancer registration as cancer had an important contribution to mortality. Further endeavors are needed to develop and strengthen cancer registration infrastructure and practices and to improve data quality and registration coverage in the PICTs.